2015
DOI: 10.1016/j.jsat.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Criminal Typology of Veterans Entering Substance Abuse Treatment

Abstract: Criminal justice involvement among veterans is a critical and timely concern, yet little is known about criminal histories and clinical characteristics among veterans seeking treatment for substance use disorders (SUDs). The present study examined criminal typology, clinical characteristics, treatment utilization, and 12-step mutual-help group (MHG) participation among veterans (N = 332) at intake to SUD treatment at the Department of Veterans Affairs (VA), and 6 months and 1 year post-intake. Cluster analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…Effect sizes indicating the strength of associations of substance use or mental health treatment with reduced legal or violence severity scores were generally in the medium to large range and were larger for patients with scores that were more severe at baseline. 44,49,[55][56][57] Improvement occurred despite the high rates of criminal involvement prior to entering opioid use, other substance use, or mental health treatment. For example, Timko et al's study found that 91% of veterans entering mental health treatment had a history of violent or non-violent offenses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Effect sizes indicating the strength of associations of substance use or mental health treatment with reduced legal or violence severity scores were generally in the medium to large range and were larger for patients with scores that were more severe at baseline. 44,49,[55][56][57] Improvement occurred despite the high rates of criminal involvement prior to entering opioid use, other substance use, or mental health treatment. For example, Timko et al's study found that 91% of veterans entering mental health treatment had a history of violent or non-violent offenses.…”
Section: Discussionmentioning
confidence: 99%
“…46 Of eight studies that examined other substance use treatment, seven reported that legal and criminal problem severity declined among veterans with alcohol or drug use disorders and among veterans with co-occurring mental health problems. [41][42][43]50,52,55 In addition, longer treatment was associated with better outcomes among alcohol and drug patients, 42,49 and treatment completion (which cannot be achieved if patients are detained or reincarcerated during treatment) was related to a lower likelihood of incarceration than was noncompletion. 51 All of these studies examined veterans entering a new episode of substance use treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to reports of Addiction and mental health office of the ministry of health of Iran (2007), from 3277 cases, 64% of HIV positive cases were infected from substance injection. Due to comorbidity of HIV/AIDS with drug consumption, injective drug abuse is a considerable health issue, because it is correlated with social problems such as violence, crime and high risk driving (20). There is drug abuse in prisons of Iran.…”
Section: Introductionmentioning
confidence: 99%